IMPROVING PRAGMATIC SKILLS OF HIGHER EDUCATION (MEDICAL) STUDENTS BASED ON INNOVATIVE AND INTERACTIVE METHODS (ACUMEN: INTERNATIONAL JOURNAL OF MULTIDISCIPLINARY RESEARCH, 2024)
In this accelerating globe, the most optimal way to increase theeffectiveness of general education is to organize lessons using interactive methods. So, what are interactive methods? What didactic possibilities do they have? What results canbe guaranteed by the appropriate and purposeful use of interactive methods in the processof mother tongue education? We will try to answer these questions in this article